SPORTS PRACTICE AS THERAPEUTIC METHOD IN PHYSICAL REHABILITATION PROGRAMS FOR CHILDREN WITH SPECIAL EDUCATION NEEDS - BAIAS, Maria-Sofia; SANDOR, Iosif (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
Our main concern consists in offering an optimal physical development rehabilitation program for children with special educational needs. The therapeutic programs we approach in special schools is based on the diversity of physiotherapy methods and playful physical activity. To increase pupil’s interest in physiotherapy sessions and to make this therapy more pleasant for these children, we introduced key elements from regular sport activities in their individual therapeutic intervention programs (e.g. basketball- played at a larger and lower positioned basket, football- played with a lighter ball in a small field, bocce- played with lightweight balls on a smaller field). These programs have been well received, no special needs child was yet to refuse playing any adapted sport for their condition. By introducing regular sports in the physiotherapy programs applied for children in our school, we succeeded to forward socialization, team-work, improving gross and fine motor skills, developing high receptivity towards sports. In order to bring out the best of their abilities, each and every child is given the opportunity and is encouraged to compete in local sports competitions organized for children with special needs. There are connections between mental and physical wellness. Maintaining physical health can also support mental well-being. In this way, everyone can use athletics as a form of treatment. This review will go into great detail on the therapeutic benefits of sport for kids, including how it can help them individually achieve better physical and emotional results and facilitate social integration. For the diversity of the therapeutic program and the healthy development of these children, as well as for the increase of their quality of life, it is necessary to integrate mainstream sports in the curriculum of special schools, as long as they are adapted to the needs of children with disabilities.